The design of the visual communication mediums, movie posters: Semiotic analyses of the posters of the movie “RECEP İVEDIK 4” - Kavuran, Tamer; Çetinkaya, Ali (My University, 2015)
A poster, which is one of the important elements of graphic arts, is a powerful visual communication medium. Technological developments and the innovations in printing techniques have been effective on the role and importance of artistic elements in poster design. In this context, poster design has gained importance in terms of the Arts-based communication. Movies require posters in terms of providing preliminary information and tips/hints about the content of the movie. In this study, the conceptual frame has been fulfilled by reviewing the index and the contents including the involved scientific journals, and in the application/ practice section, on the other hand, the posters of the first watched movies in the Turkish Cinema, ‘Recep İvedik 4’, have been analyzed in terms of graphics through the interpretational methods of semiotics. As the result of the analysis, results and suggestions regarding the semiotic interpretations in the movie posters that are the visual communication mediums have been presented.
Bildiri - Yayımlanmış
Keywords: Poster; Semiotics; Turkish cinema; Graphic design